1999
DOI: 10.1099/00221287-145-10-2663
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of enteric bacteria from Australian mammals: host and geographical effects

Abstract: Bacteria of the family Enterobacteriaceae were isolated from 642 mammalian hosts, representing 16 families and 79 species, collected from throughout Australia. Escherichia coli was the most common of the 24 enteric species recovered and represented almost half of the isolates. Association analysis revealed that most other species of bacteria were less likely to be recovered from hosts in which E. coli was present. The composition of the enteric community of a host was found to be determined by both the taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 32 publications
3
86
1
2
Order By: Relevance
“…That is, the specificity for Salmonella in causing disease more readily in particular hosts may be intimately associated with that serovar's ability to avoid the predators within that host; Salmonella must avoid predation before it invades intestinal epithelium. Consistent with this hypothesis, Salmonella and E. coli have been found to be differentially distributed among the intestinal environments of their hosts (Boyd et al, 1993;Gordon & FitzGibbon, 1999;Gordon et al, 2002;Gordon & Cowling, 2003;Rabsch et al, 2002). We found similar results here where, for example, the serovars of Salmonella within turtles and bearded dragons were significantly different from those we isolated from birds (Table 1).…”
Section: Differential Distribution Of Salmonella May Results From Predsupporting
confidence: 81%
“…That is, the specificity for Salmonella in causing disease more readily in particular hosts may be intimately associated with that serovar's ability to avoid the predators within that host; Salmonella must avoid predation before it invades intestinal epithelium. Consistent with this hypothesis, Salmonella and E. coli have been found to be differentially distributed among the intestinal environments of their hosts (Boyd et al, 1993;Gordon & FitzGibbon, 1999;Gordon et al, 2002;Gordon & Cowling, 2003;Rabsch et al, 2002). We found similar results here where, for example, the serovars of Salmonella within turtles and bearded dragons were significantly different from those we isolated from birds (Table 1).…”
Section: Differential Distribution Of Salmonella May Results From Predsupporting
confidence: 81%
“…The manner in which the characterized isolates were obtained has varied among studies, and these isolates may represent clones collected from single populations, clinical isolates, or subsamples of strains collected in an ad hoc fashion. Recent work has demonstrated that a number of species of enteric bacteria are non-randomly distributed with respect to either the taxonomic family of the host from which they were isolated or the geographical locality where the host was collected (Gordon & FitzGibbon, 1999). Such an observation demonstrates the existence of population structure and suggests that these species may exhibit adaptations specific to particular types of primary (host environment) and secondary (external environment) habitats (sensu Savageau, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Faecal swabs were obtained from a variety of mammalian hosts representing 79 species from 16 families collected from over 75 localities throughout Australia (Gordon & FitzGibbon, 1999). Primary isolation of the strains was performed by streaking the swabs for single colonies on a MacConkey agar plate (Power & McCuen, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, E. coli will only be detected if it represents, on average, more than 1 % of the total number of bacterial cells capable of growth on this medium. MacConkey medium is non-selective with respect to members of the Enterobacteriaceae (Ewing, 1986), but it inhibits the growth of Gram-positive and many Gramnegative species, to the extent that about 92 % of the bacteria recovered from mammals were members of the Enterobacteriaceae (Gordon & FitzGibbon, 1999). Relative to other members of the Enterobacteriaceae, E. coli has a distinct colony morphology and colour on MacConkey agar and consequently is unlikely to be overlooked.…”
Section: Definition Of Prevalencementioning
confidence: 99%
“…However, in a study of E. coli isolated from non-domesticated Australian mammals, Gordon & FitzGibbon (1999) showed that the probability of isolating E. coli from an individual depended on the taxonomic family of the host and on the geographic locality from which the host was collected. In an investigation of the genetic structure of E. coli isolated from Australian mammals using the technique of multi-locus enzyme electrophoresis, Gordon & Lee (1999) demonstrated that host taxonomic family and geographic locality explained a small but significant amount of the observed genetic variation.…”
Section: Introductionmentioning
confidence: 99%